Pembagian Masker Kepada Warga Desa Grendeng, Kabupaten Banyumas Sebagai Pencegahan Penyebaran Covid-19 Tahun 2021 - Huwaida Yuko Salsabila (Abdi Jaya : Jurnal Pengabdian Indonesia, 2024)
WHO officially declared Covid-19 a global pandemic, with the first case in Indonesia reported in March 2020. In January 2021, there was a spike in cases in Indonesia, one of which was caused by low public awareness of implementing health protocols, especially in the use of masks. As one solution, free masks were distributed to residents of Grendeng Village. This program aims to reduce the spread of Covid-19 while providing education on how to use masks properly (covering the mouth and nose) and providing an appeal to always wear masks when doing activities outside the home, according to government recommendations. The methods used in this activity were direct assistance and surveys. The results showed an increase in public awareness of the importance of using masks when leaving the house to prevent the spread of Covid-19.